How Does the Beauty of Wives Affect Post-Marriage Family Outcomes? Helen's Face in Chinese Households - Junsen Zhang; Shulan Fei; Yanbing Wen (Institute of Labor Economics (IZA), 2023)
Research on the economics of beauty has persistently emphasized beauty premiums in the labor market but ignored its influence within existing marriages. We examine the physical appearance of the wives and its influence on several post-marriage family outcomes using a conceptual framework that is widely applicable. Based on two data sets from China, we find beautiful women have at least 0.43 fewer children than average- or plain-looking women when controlling for other factors. The negative effect remains robust controlling for wages and the possible endogeneity of beauty. In terms of mechanisms, the negative impact seems to operate by altering bargaining power within the family and the opportunity cost of having children, but not through the quantity-quality interaction of children. For other outcomes, wives' good looks reduce the probability of their taking care of or tutoring their children and increase the probability of parents or in-laws caring for children or performing household chores in urban areas.
Keywords: J10; J13; 330; beauty; household bargaining power; number of children; intergenerational care; opportunity cost